Management of the External Value of the Renminbi - Heikki Oksanen (Center for Economic Studies and ifo Institute (CESifo), 2015)
Pegging the renminbi (RMB) to the US dollar since 1994 has characterised China's exchange rate policy, under either a fixed peg or appreciating crawling peg. The current policy, announced in June 2010, of `floating with reference to a basket' has now in April 2015 made the RMB 19 per cent stronger against a trade-weighted basket, while it is nine per cent stronger against the USD. Ten percentage points thus arise from changes in the cross rates of the other currencies. This effect could be eliminated by managing the external value of the RMB with reference to a genuine broad basket. This could be a suitable intermediary exchange rate regime for China as the risks of jumping to free floating are still great. Diversifying further the currency composition of the foreign exchange reserves and other foreign assets of the Chinese government, from USD towards EUR and JPY assets, would be a natural parallel shift. The current EUR-USD-JPY exchange rates may offer a good opportunity to carry out this move.
Keywords: F30; F31; F33; F42; 330; China; renminbi; yuan; basket peg; foreign exchange rates